Implementasi Kegiatan Muhadharrah dan Kontribusinya terhadap Karakter Religius Siswa Kelas VII SMPN 5 Padang Panjang - Putri, Cyntia Tiara; Kanus, Oktari (Darul Yasin Al Sys, 2025)
The low level of religious character among some seventh-grade students at SMPN 5 Padang Panjang, as reflected in negative behaviors such as using foul language, cheating, skipping congregational prayers, and showing disrespect toward teachers and peers, forms the background of this study. This is despite the school's implementation of muhadharah activities every Friday morning as part of its efforts to foster students' religious character. The study aims to describe the implementation of muhadharah activities, their contribution to students’ religious observance in terms of worship practices, and the supporting and inhibiting factors affecting their execution. This field-type qualitative study involved the vice principal for student affairs, three Islamic Religious Education (PAI) teachers, and three seventh-grade students from each class as subjects. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that muhadharah has become a routine agenda that encourages active student participation and contributes to religious knowledge enhancement, as well as the development of speaking skills, courage, creativity, and self-confidence. The activity also positively contributes to the development of religious character, particularly in worship practices such as prayer, fasting, Qur’an recitation, almsgiving, and supplication. Supporting factors include backing from the Education Service, the school's vision and mission, school leadership, involvement of the student council (OSIS) and teachers, and the availability of facilities and funding. Inhibiting factors include weather conditions, students’ lack of focus, limited time, and suboptimal preparation.